Participatory Social Mapping For Cocoa Farming Development Interventions in Polewali Mandar, Indonesia - Kautsar, Muthia Natasya; Sainab (Program Studi Agribisnis Universitas Muhammadiyah Sinjai, 2025)
Modern agricultural development requires not only technological innovation but also a deep understanding of social and institutional dynamics. This study employs Participatory Social Mapping (PSM) to analyze social structures and actor networks within cocoa farming communities in Polewali Mandar. Using purposive sampling, five key informants were selected: four leaders of cocoa farmer groups who are still active in cocoa cultivation and one local cocoa enterprise, PT. Indonesia Hijau. Data were examined through qualitative descriptive analysis combined with Social Network Analysis (SNA) to map relationships and identify central actors. Results show that cocoa farmers form strong, multi-layered networks. Internally, interactions occur within farmer groups in Luyo, Tutar, Mapilli, and Tapango, serving as hubs for knowledge sharing. Externally, farmers are linked with supporting institutions such as PT. Mars (development), Barry Callebaut (seed supply), PT. Indonesia Hijau (collaboration), and the UIH Cooperative (distribution and marketing). These networks are marked by openness and collaboration, with farmers as central actors. Despite geographical constraints, communication is sustained both physically and virtually. The UIH Cooperative emerges as the most connected and influential actor due to its daily engagement in farmers’ socio-economic activities. Supporting institutions contribute to innovation, sustainability, and input provision. The study highlights the critical role of social capital and institutional connectivity in advancing sustainable cocoa farming and effective agricultural extension.